2012
DOI: 10.1177/0161734612455580
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic-Based Assessment of Myocardial Fiber Structure in Individual, Excised Hearts

Abstract: The objective of this study was to assess the feasibility of using echocardiographic imaging as an approach for determining the myocardial fiber structure of intact, individual hearts. Seven formalin-fixed, ex vivo sheep hearts were imaged using a commercially available echocardiographic imaging system, and the intrinsic fiber structure for the reconstructed short-axis cross section was determined for a specific distance from the apex of each heart. Diffusion tensor magnetic resonance (DT-MR) images of each he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…(Milne et al 2012) That study, limited to 2D short-axis reconstructions, found that echocardiographic-based measurements of fiber structure in a specific transverse plane qualitatively agreed with the corresponding estimates obtained using diffusion tensor magnetic resonance imaging (MRI) methods. The objective of the current study is to extend the previous work on single planes of the heart by demonstrating the feasibility of creating quantitative myofiber multiplane structure maps over the entire volume of intact hearts based on 3D echocardiographic information.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…(Milne et al 2012) That study, limited to 2D short-axis reconstructions, found that echocardiographic-based measurements of fiber structure in a specific transverse plane qualitatively agreed with the corresponding estimates obtained using diffusion tensor magnetic resonance imaging (MRI) methods. The objective of the current study is to extend the previous work on single planes of the heart by demonstrating the feasibility of creating quantitative myofiber multiplane structure maps over the entire volume of intact hearts based on 3D echocardiographic information.…”
Section: Introductionsupporting
confidence: 54%
“…(Milne et al 2012) In brief, after fixation preparation was completed, each heart was placed base-down in a cylindrical water-filled tank in preparation for collecting backscatter data. A series of apical echocardiographic images, in 5-degree rotational increments about the apex of each heart, were obtained using a General Electric Vivid 7 clinical imaging system (GE Healthcare, Wauwatosa, WI, USA) at a nominal center frequency of 5.0 MHz in fundamental imaging mode (Figure 1a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional imaging techniques have the capability to improve heart disease diagnosis and outcomes. Among the cardiac imaging systems are also ultrasound [5658], chest X-ray [59, 60], cardiac catheterization [61, 62], magnetic resonance imaging (MRI) [52, 63, 64], computerized tomography (CT) [65, 66], cardiac positron emission tomography (PET) [6769], cardiac single-photon emission computed tomography (SPECT) [70], and intravascular ultrasound [71, 72]. Ultrasound allows for non-invasive visualization of blood flow through the heart using Doppler [73].…”
Section: Overview Of Imaging Technologies For Detecting Heart Failurementioning
confidence: 99%
“…Some animal models that have been used with these imaging protocols for HF studies are rat [76, 77], canine [2, 10, 50, 78, 79], rabbit [12, 80], pig [81], sheep [56, 80, 82], and mice [14, 83]. Figure 3 shows representative DT-MRI images of hearts from a mouse, a rabbit, and a sheep.…”
Section: Overview Of Imaging Technologies For Detecting Heart Failurementioning
confidence: 99%